Supplier selection problem in IoT solutions. Issue 1 (1st April 2019) - Agarwal, Sonal; Sharma, Vidushi; Pughat, Anuradha
Abstract : Purpose: The use of Internet of Things (IoT) and networks has built a potential impact on the product cost and time in a company's manufacturing process. These IoT solutions provide end-to-end visibility and faster introduction of merchandise and supplier in the market. The main aim of this research paper is to supply products with improved quality and cheaper price, whereas the rising response and quality of the client service. Design/methodology/approach: This paper designs and develops two cases for selecting the most efficient vendor while keeping in mind the profit and cost constraints in optimization. Findings: Outsourcing is a vital parameter to cut back the price and maximize the profit of the manufacturer. Therefore, the integration of supply chain with IoT can provide a solution to the cost optimization and supplier/vendor selection problems in supply chain management. Research limitations/implications: The results show that the models are quite realistic and can help the IoT-based manufacturing units to make strategic decisions regarding product manufacturing and distribution. Practical implications: The authors can further extend the model to derive the retailer's profit function and develop the end product cost to the consumers and hence make it a n -level multi-vendor selection model for IoT-based systems. Originality/value: The right choice of vendor for IoT-enabled business is a crucial concern. In this paper, the authors designed and developed multi-vendor models with in-house production and outsourcing decisions to meet the demand along with the vendor selection. The variable demands and designed variable unit cost function and batch order are set to make vendor selection more realistic.